2010
DOI: 10.2355/isijinternational.50.44
|View full text |Cite
|
Sign up to set email alerts
|

Deoxidation Equilibrium of Titanium in the Iron–Nickel Melts

Abstract: The oxygen solutions in the titanium-containing Fe-Ni melts have been thermodynamically analyzed. When the nickel content rises to 40 %, the deoxidation ability of titanium decreases but then it sharply rises with increasing nickel concentration in melt. This can be explained by the fact that although the bond strength of titanium in nickel is considerably stronger in comparison with iron (g°T i(s)(Fe) ϭ0.0083; g°T i(s)(Ni) ϭ0.00019), but the bond strength of oxygen in nickel is appreciably weaker that in iron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 26 publications
(22 reference statements)
0
6
0
3
Order By: Relevance
“…3 in comparison with similar data on the dependence of oxygen solubility in this melt on content of chromium [11], manganese [12], vanadium [13], silicon [12], carbon [14], titanium [15], and alu minum [16]. It can be seen that aluminum possesses the highest oxidizing ability among the studied ele ments; zirconium also shows fairly high oxidizing abil ity.…”
Section: Resultsmentioning
confidence: 64%
“…3 in comparison with similar data on the dependence of oxygen solubility in this melt on content of chromium [11], manganese [12], vanadium [13], silicon [12], carbon [14], titanium [15], and alu minum [16]. It can be seen that aluminum possesses the highest oxidizing ability among the studied ele ments; zirconium also shows fairly high oxidizing abil ity.…”
Section: Resultsmentioning
confidence: 64%
“…Different phases can be precipitated using different titanium amount [16] in the Fe-Ni deoxidation. Suzuki et al [17] reported that the FeO solubility in the TiO 2 phase is much higher than that in the Ti 3 O 5 phase.…”
Section: Thermodynamic Consideration Of Critical Ti Contentmentioning
confidence: 99%
“…A simplified model to evaluate the capillary force can be expressed as Eq. (16). The details of the equations deviation can be found elsewhere [52,53].…”
Section: Agglomeration Of the Oxide Particles At The Surface Of The Mmentioning
confidence: 99%
See 1 more Smart Citation
“…Равновесные концентрации алюминия и кислорода в расплавах никеля при 1873 К, % -1,535 [9] 0,036 [9] -0,355 [14] Для расплавов никеля, содержащих титан и кислород, величина параметра может быть использована до содержания титана 5 % [9].…”
unclassified